Regulation of nitrogenase activity by oxygen in Azospirillum brasilense and Azospirillum lipoferum. - Hartmann, A (1987)
The nitrogenase activity of the microaerophilic bacteria Azospirillum brasilense and A. lipoferum was completely inhibited by 2.0 kPa of oxygen (approximately 0.02 atm of O2) in equilibrium with the solution. The activity could be partially recovered at optimal oxygen concentrations of 0.2 kPa. In contrast to the NH4+ switch off, no covalent modification of the nitrogenase reductase (Fe protein) was involved, as demonstrated by Western-blotting and 32P-labeling experiments. However, the inhibition of the nitrogenase activity under anaerobic conditions was correlated with covalent modification of the Fe protein. In contrast to the NH4+ switch off, no increase in the cellular glutamine pool and no modification of the glutamine synthetase occurred under anaerobic switch-off conditions. Therefore, a redox signal, independent of the nitrogen control of the cell, may trigger the covalent modification of the nitrogenase reductase of A. brasilense and A. lipoferum.